Ion Exchange Resin Catalyzed Synthesis of Substituted-4-methyl-3-(substituted phenoxy)coumarins - Rathnam, M.V.; S. Thatte, Chittaranjan; C. Pise, Abhinay (Asian Journal of Chemistry, 2010)
Various substituted 2H-1-benzopyran-2-one-4-methyl-3-(substituted phenoxy)compounds have been successfully synthesized by the reaction of ethyl-2-(substituted phenoxy)-3-oxobutanoates (Ia-Id) with resorcinol, 4-chloro resorcinol and a-naphthol using ion exchange resins such as Amberlyst-35 and K-2641, with and without solvent. The catalyst was reused without much loss of yield. The homogeneity of these compounds was established by the HPLC analysis of pure compounds. The characterization of the compounds was done on the basis of 1H NMR, IR, mass spectrometry and elemental analysis. The compounds have been tested for their antibacterial activity.